The discovery of a key prenyltransferase gene assisted by a chromosome-level Epimedium pubescens genome - Shen, Guoan; Luo, Yanjiao; Yao, Yu; Meng, Guoqing; Zhang, Yixin; Wang, Yuanyue; Xu, Chaoqun; Liu, Xiang; Zhang, Cheng; Ding, Gang; Pang, Yongzhen; Zhang, Hui; et al. (Frontiers in Plant Science, 2022)
Epimedium pubescens is a species of the family Berberidaceae in the basal eudicot lineage, and a main plant source for the traditional Chinese medicine "Herba Epimedii". The current study achieved a chromosome-level genome assembly of E. pubescens with the genome size of 3.34 Gb, and the genome guided discovery of a key prenyltransferase (PT) in E. pubescens. Our comparative genomic analyses confirmed the absence of Whole Genome Triplication (WGT-) event shared in core eudicots and further revealed the occurrence of an ancient Whole Genome Duplication (WGD) event approximately between 66 and 81 Million Years Ago (MYA). In addition, whole genome search approach was successfully applied to identify 19 potential flavonoid PT genes and a flavonoid PT (EpPT8) was proven to be an important enzyme in the biosynthesis of medicinal compounds, icaritin and its derivatives in E. pubescens. Therefore, our results not only provide a good reference genome to conduct further molecular biological studies in Epimedium genus, but also give important clues for synthetic biology and industrial production of related prenylated flavonoids in future.